Food Sovereignty and Agricultural Policy of Egypt - V. A. Isaev; A. O. Filonik (Мир новой экономики, 2021)
The material conditions for countries and peoples’ existence are now changing signifiantly and sharply and put forward new requirements for the quality of reproductive mechanisms. To a large extent, this process is related to the village, which seeks to increase agricultural productivity, but cannot yet become on a par with industrial potential. The gap between these two parts of a single economic organism is large and is especially noticeable in developing countries and, in particular, in Egypt. This country is extremely poor in agricultural resources; it has been trying for decades to overcome the threat of hunger, sometimes achieving moderate success in some areas. But on the whole, it can only follow events in a catch-up mode. Now Egypt is entering a new phase of the struggle for food sovereignty and an unclear fial result. However, the state’s current policy is focused on making food security solvable.